Utilisation of geriatric assessment in oncology - a survey of Australian medical oncologists. Issue 2 (March 2019) - To, Timothy H.M.; Soo, Wee Kheng; Lane, Heather; Khattak, Adnan; Steer, Christopher; Devitt, Bianca; Dhillon, Haryana M.; Booms, Anne; Phillips, Jane
Abstract: Introduction: Geriatric assessment (GA) is a multidimensional health assessment of the older person to evaluate their physical and cognitive function, comorbidities, nutrition, medications, psychological state, and social supports. GA may help oncologists optimise care for older patients with cancer. The aim of this study was to explore the views of Australian medical oncologists regarding the incorporation of geriatric screening tools, GA and collaboration with geriatricians into routine clinical practice. Methods: Members of the Medical Oncology Group of Australia were invited to complete an online survey that evaluated respondent demographics, practice characteristics, treatment decision-making factors, use of GA, and access to geriatricians. Results: Sixty-nine respondents identified comorbidities, polypharmacy, and poor functional status as the most frequent challenges in caring for older patients with cancer. Physical function, social supports and nutrition were the most frequent factors influencing treatment decision-making. The majority of respondents perceived value in GA and geriatrician review, although access was a barrier for referral. Such services would need to be responsive, providing reports within two weeks for the majority of respondents. Conclusion: Despite an emerging evidence base for the potential benefits of GA and collaboration with geriatricians, medical oncologists reported a lack of access but a desire to engage with these services.